Securing US influence in Asia Pacific : the military angle - Harshita Kohli (2014)
Although economic and diplomatic domains of the US pivot dominate discussions, the military angle cannot be ignored. This dimension consists of two pillars: Air sea Battle to offset China’s Anti-Access and Area Denial capabilities and closer military relations with allies in the Asia Pacific.